2011
DOI: 10.1002/ejlt.201000299
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐metathesis of methyl 10‐undecenoate with diethyl maleate: Formation of an α,ω‐diester via a metathesis reaction network

Abstract: Cross-metathesis of methyl 10-undecenoate with diethyl maleate: Formation of an a,v-diester via a metathesis reaction network Arno Behr, Jessica Pé rez Gomes and Zeynep Bayrak Department of Biochemical and Chemical Engineering, Technische Universitä t Dortmund, Dortmund, GermanyThe cross-metathesis of methyl 10-undecenoate 1 derived from castor oil as a renewable raw material with diethyl maleate 2 was investigated. These reactions were carried out with several phosphine and Nheterocyclic carbene ruthenium cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…In some examples it was shown that acrylonitrile inhibits the ruthenium-catalysed cross-metathesis of functional alkenes, whereas methyl acrylate does not inhibit this reaction as some cross-metathesis can be performed in bulk in methyl acrylate [16,17,[70][71][72]. Thus, it appeared that the linear amino ester 18 could also arise from the cross-metathesis of the 10-undecenenitrile 21 with methyl acrylate followed by hydrogenation.…”
Section: Cross-metathesis Of Renewable 10-undecenenitrile and Methyl mentioning
confidence: 99%
“…In some examples it was shown that acrylonitrile inhibits the ruthenium-catalysed cross-metathesis of functional alkenes, whereas methyl acrylate does not inhibit this reaction as some cross-metathesis can be performed in bulk in methyl acrylate [16,17,[70][71][72]. Thus, it appeared that the linear amino ester 18 could also arise from the cross-metathesis of the 10-undecenenitrile 21 with methyl acrylate followed by hydrogenation.…”
Section: Cross-metathesis Of Renewable 10-undecenenitrile and Methyl mentioning
confidence: 99%
“…At the same period, this group also investigated the cross metathesis of methyl 10-undecenoate 72 (arising from the pyrolysis of castor oil) with diethyl maleate 73 leading to the diester 74 (Scheme 25). [117] Experimental parameters as well as various ruthenium-based catalysts were investigated. Again, the best results were obtained with a high catalyst loading (4 mol%) of the indenylidene catalyst Ru21 and the formation of the self-metathesis product of 72 could not be reduced below 25%.…”
Section: Cross Metathesis With Functional Olefinsmentioning
confidence: 99%
“…Diethyl maleate as a co‐substrate affords the corresponding C12‐diester in high yields of 91% under optimized reaction conditions. The reaction is carried out at 70°C with 4 mol% of the catalyst Neolyst M2 for 3 h in toluene at a molar substrate ratio of 1:6 in favor of diethyl maleate . The cross‐metathesis with dimethyl maleate is even more active, yielding almost quantitative yields for dimethyl 2‐dodecenoate in only 1 h at 80°C in toluene with a substrate ratio of 1:5 and a low catalyst loading of only 0.75% Neolyst M2 .…”
Section: Metathesismentioning
confidence: 99%